Sustained drug released from contact lens - Ferreira, J. A. (2009)
This paper focuses on ophthalmic drug release from a loaded copolymer: the drug is dispersed in the polymeric matrix and entrapped in particles. The copolymer is based in 2-hydroxyethyl methacrylate co-methacrylic acid and silicone is used to prepare the loaded particles. A mathematical model to simulate the drug release is proposed and a qualitative analysis is performed. Experimental results are compared with simulation results. Contact lens made from the presented copolymer are expected to deliver drug at therapeutical levels for a few days.